Literasi Bahaya Hoax pada Masyarakat Kelurahan Sumur Meleleh Kecamatan Teluk Segara Kota bengkulu - Octaviani, Vethy; Asnawati, Asnawati; Sariningsih, Marida (Jurnal Dehasen Mengabdi, 2022)
Handling the spread of hoaxes is important because it is a form of pro-active and university participation, so the community service team of the Communication Studies Program Faculty of Social Sciences, Dehasen University Bengkulu in collaboration with the National Media liputan6.com carried out community service activities with the theme 'Filter Before Sharing ; Stop The Deception, Let's Embrace The Truth Together' with the aim of helping to create peace and comfort in social life in order to avoid hoaxes and as hoax spreaders. This activity was carried out on Pariwisata Street Sumur Meleleh Village, Teluk Segara District, Bengkulu City. Implementation of activities by going directly to the community door to door distributing ‘Stop Hoax’ leaflets from Liputan6.com while discussing with the community. From the results of conversations, with several people, few know about hoaxes and do not know how to distinguish the truth of a news story. The team educates the public by providing tips to avoid hoaxes, for example by checking the website address to find out information obtained from the website or including a link, namely by observing the URL address of the site in question, checking facts by paying attention to where the news comes from and who the source is (whether from an institution or institution). official), pay attention to the balance of news (not just from one source), and check the authenticity of photos. That is, before believing a news we must research it first.